2010
DOI: 10.1177/1469787410365658
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between student engagement and transition

Abstract: Failure to establish meaningful and effective transition for undergraduates can lead to academic underachievement. Student engagement represents a key component of student success. This study sought to investigate the impact of a bespoke transition programme featuring a wide range of innovative, student-centred activities on enhancing students' engagement with educationally effective practices through examining student relations with others, learning and the discipline. For the study 104 undergraduates on a Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…The International Association of Universities acknowledges: "access without a reasonable chance of success is an empty phrase" (Devlin, 2013: 939). Globally, this imperative has prompted research interest into how various student cohorts' experience transition and transition within the university environment (see for example Johnston, 2010;O'Shea, 2014;Vinson, Nixon, Walsh, Walker, Mitchell, & Zaitseva, 2010;Wawrzyniski, Heck & Remley, 2012). However, within Australia, student attrition remains a significant issue and, whilst rates have decreased, the latest figures (ABS, 2012) suggest approximately 12.8% of the total Australian student population leaves university prior to completion.…”
Section: Introductionmentioning
confidence: 99%
“…The International Association of Universities acknowledges: "access without a reasonable chance of success is an empty phrase" (Devlin, 2013: 939). Globally, this imperative has prompted research interest into how various student cohorts' experience transition and transition within the university environment (see for example Johnston, 2010;O'Shea, 2014;Vinson, Nixon, Walsh, Walker, Mitchell, & Zaitseva, 2010;Wawrzyniski, Heck & Remley, 2012). However, within Australia, student attrition remains a significant issue and, whilst rates have decreased, the latest figures (ABS, 2012) suggest approximately 12.8% of the total Australian student population leaves university prior to completion.…”
Section: Introductionmentioning
confidence: 99%
“…The poster group exercise (consisting of five students) and personal tutor-led workshops (ten students) are the heart of the process facilitating engagement with peers and staff. The part played by personal tutors during the transition process is important and has been recognised in many previous studies (Owen 2002;Vinson et al 2010) and it has often been suggested that induction processes benefit from splitting large cohorts of students into small groups (Glogowska, Young, and Lockyer 2007).…”
Section: The Transition Process Being Measuredmentioning
confidence: 99%
“…Longden (2006) suggests that this carries the danger of creating 'knee-jerk reactions' and ineffective interventions. We also hoped to contribute to the wider debate between those tending to advocate shorter (Longden 2006), or longer (Vinson et al 2010), transition strategies. Finally, could we find evidence to justify the commitment of staff and student time?…”
Section: The Aim Of This Studymentioning
confidence: 99%
“…The BNIM interview method allows interviewees to construct their own lived experience as free as possible from any researcherinfluenced bias, and offers rich description of the participant experience. This project is informed by previous research, such as Tinto (1997) and Astin (1973), as well as a consideration of broader themes identified by other studies, such as individual culture and self-perception (Chow and Healy, 2008;de Beer, Smith and Jansen, 2009), university branding and the physical environment (Dixon and Durrhiem, 2004), induction events and transition (Vinson et al, 2010), teaching and group belonging (Hamilton, McFarland and Mirchandani, 2000;Levett-Jones and Lathlean, 2008).…”
Section: Introductionmentioning
confidence: 99%